2000
DOI: 10.1023/a:1017523230758
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This paper describes a research project that had two goals: (1) to design and develop a tool with which to investigate pupils' images of mathematicians; and (2) to use the device to compare those images held by lower secondary pupils (ages 12-13) in five countries. We report that with small cultural differences certain stereotypical images of mathematicians are common to pupils in all of these countries and these images indicate that for pupils of this age mathematicians and the work that they do are, for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 23 publications
5
42
1
1
Order By: Relevance
“…Finson (2002) also considered the extension of Chambers' (1983) seven stereotypical elements in the DAST-C introduced in 1995 by Finson, Beaver and Cramond (1995). The DAST has been further adapted to access images of engineers (Knight & Cunningham, 2004;Thompson & Lyons, 2008) and mathematicians (Pickle & Berry, 2000).…”
Section: Accessing Stem Images With Drawing-based Instrumentsmentioning
confidence: 99%
“…Finson (2002) also considered the extension of Chambers' (1983) seven stereotypical elements in the DAST-C introduced in 1995 by Finson, Beaver and Cramond (1995). The DAST has been further adapted to access images of engineers (Knight & Cunningham, 2004;Thompson & Lyons, 2008) and mathematicians (Pickle & Berry, 2000).…”
Section: Accessing Stem Images With Drawing-based Instrumentsmentioning
confidence: 99%
“…An interesting observation is that in neither country was there a negative attitude towards the teacher found in the drawings. This is unlike the results of the findings of Picker and Berry (2000), where the drawings of the teacher showed that they did not always have control over the group of students or the content being taught. Instead, in our study, in both countries the interaction between a teacher and students seemed to be positive in the drawings.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Despite the potential of investigating YA literature to view commonly discussed ideas in our society, mathematics has rarely been a focus. Furthermore, although the images of mathematics as a subject have been explored by looking into students' drawings (Picker & Berry, 2000), advertisements and films (Evans, Tsatsaroni, & Staub, 2007), and in many other forms, we encourage teachers and other scholars to analyze with young readers the issues of identity and belonging, stereotyping and discrimination, and the potential for productive identifying as a mathematical doer and learner.…”
Section: Mathematics Learning Experiences In Ya Literaturementioning
confidence: 99%